Etiology and phenomenology of economic criminality in transitional societies - Kostic, Jelena Ž (Sociološki pregled, 2024)
There is no generally accepted definition of economic criminality. The reason for this may be the frequent change of its content, i.e., of the criminal acts it includes. Together with the development of socio-economic relations, new forms of the mentioned type of criminality also develop, so perhaps the definition neither should nor could be universal. Transitional societies have faced significant changes both in the field of political organization and in the field of economy. The most noticeable consequences of transition and switching to market economy were high unemployment and social stratification of the population. This had a negative impact on social values and morality, and therefore led to an increase in criminality.The aim of this research is to indicate the causes and forms of economic criminality in transitional societies. We start from the assumption that timely preparation for significant social changes, in terms of establishing adequate legal regulations and the existence of independent control mechanisms of certain economic processes, is of great importance for the prevention of economic crimes. By applying the content analysis, we try to show that even the countries in which the process of political and economic transition has long since ended can also face problems that potentially contribute to a large number of perpetrators of crimes that fall within the domain of economic criminality remaining unpunished, which directly threatens the principle of the rule of law.
Keywords: economic criminality; etiology; phenomenology; transition